The effect of using quarry dust as a sand replacement material on compressive strength of concrete - Muhamad Shyamir Al Amar , Muhamad Tobib (2012)
Common river sand is expensive due to excessive cost of transportation from natural sources. Also large-scale depletion of these sources creates environmental problems. As environmental transportation and other constraints make the availability and use of river sand less attractive, a substitute or replacement product for concrete industry needs to be found. River sand is most commonly used fine aggregate in the production of concrete poses the problem of acute shortage in many areas. Whose continued use has started posing serious problems with respect to its availability, cost and environmental impact. Otherwise, in such a situation the quarry dust can be an economic alternative to the river sand. quarry dust can be defined as residue, tailing or other non-voluble waste material after the extraction and processing of rocks to form fine particles less than 4.75mm. Usually, quarry dust is used in large scale in the highways as a surface finishing material and also used for manufacturing of hollow blocks and lightweight concrete prefabricated Elements. Use of quarry dust as a fine aggregate in concrete draws serious attention of researchers and investigators. Therefore, this study is the use of quarry dust, which is inert material or waste that is not useful, as a substitute for sand in concrete. The main objective of the implementation of this study was to determine the optimum content suitable quarry dust and workability of concrete containing quarry dust vary. The samples were prepared in the laboratory sample cubes with quarry dust composition from 0% to 25% where each sample is added 5% quarry dust. From the results, the optimum content of quarry dust which reached a maximum strength is 5%. Workability while decreasing with increasing quarry dust.